Nutrigenomic profiling identifies ZIP10 ( SLC39A10 ) as a regulator of erythroid zinc homeostasis with genetic associations to anemia risk - Juyoung Kim; Yitang Sun; Kaixiong Ye; Jaekwon Lee; Robert J. Cousins; Moon-Suhn Ryu (Proceedings of the National Academy of Sciences, 2026)
Erythroid progenitors undergo dynamic morphological changes and robust heme biosynthesis during differentiation. Zinc is essential for erythropoiesis, yet the mechanisms linking zinc availability to heme biosynthesis and anemia risk remain unclear. This study aimed to define zinc-responsive pathways in differentiating erythroid progenitors and to evaluate the translational relevance of SLC39A10 ( ZIP10 ) genetic variants to hematological health. To elucidate the molecular basis of zinc’s role in erythropoiesis, we performed transcriptomic profiling of zinc-restricted G1E-ER4 cells during differentiation and compared it to iron chelation and δ-aminolevulinic acid dehydratase inhibition. Zinc deficiency uniquely enriched genes involved in not only heme biosynthesis but cellular maintenance functions. Zinc restriction caused a marked suppression of Alad transcript abundance, impairing the first enzymatic step of cytosolic heme biosynthesis. Notably, Slc39a10 ( Zip10 ) was the only zinc transporter strongly induced by zinc deficiency, independent of iron status. Loss of ZIP10 exacerbated zinc depletion, further reduced Alad expression, and diminished heme output, highlighting its role as a compensatory importer during zinc scarcity. GWAS database analyses revealed that SLC39A10 variants are significantly associated with hemoglobin concentration, hematocrit, and iron deficiency anemia risk. Together, ZIP10 safeguards erythroid zinc homeostasis and heme synthesis under limiting zinc conditions. Genetic variation in SLC39A10 may heighten sensitivity to zinc deficiency, providing a potential nutrigenetic marker for anemia risk. These findings establish a mechanistic and translational basis for genotype-guided precision nutrition strategies to improve hematological health.